Principles of Agricultural Landscapes Durability Formation by the Example of Poltava Region - Lytvynenko, Tetiana; Lvovska, Tetiana; Mishchenko, Roman; Harmash, Valerii (International Journal of Engineering and Technology, 2018)
Land resources usage of Poltava region for their functional use is analyzed. Based on the research data analysis, the principles of agricultural landscapes durability formation are created and formed into 4 groups: territorial differentiation, environmental friendliness, maintenance checkup, law-regulatory and controlling.Â Â